Space Interpretation of the Installation Art (Al-Academy, 2021)
The research dealt with the study (interpretation of space in the art of installation), and it is located in four frameworks, the first is devoted to clarifying the research problem, its importance and the need for it, its goal, and its limits, and determining the most important terms contained therein.The research problem was determined from the question, does space embody those different and diverse materials that were formulated and installed by the artist into modern forms? Is the product of synthetic arts an appropriation of these spaces and domination of them?The problematic of interpreting space in its conceptual dimension in (synthetic) art in its multiplicity, diversity and difference, or objecting to the work of artistic systems in the time of modernity, as they are spaces with a formal format closed within the framework of artistic work, but now, in the midst of the intertwining of arts and scientific progress with its technological means and contemporary critical theories, it has led to the disruption of Previous theories and their uselessness in reading and analyzing contemporary space systems. and its deliberation in contemporary societies. The theoretical framework included two sections: the first topic was concerned with the concept of space and temporal space, and with a review of some philosophical opinions in this concept. The second topic dealt with: Artistic space patterns in the plastic field and research in the foundational references for installation art in modern and contemporary art movements.As for the research procedures: the research community was identified and its sample of (3) artworks was selected, then the treatments of the research tool and the method of its construction were reviewed, and the sample was analyzed. The fourth chapter included results, conclusions and suggestions